Effects of Escitalopram on C reactive protein in patients of depression - Gaurav Chittora; Pali Rastogi; Ramghulam Razdan; Prafulla Songara (International Journal of Medical Research and Review, 2017)
Objective: To study the anti-inflammatory activity of Escitalopram in newly diagnosed patients of depression.Materials and Methods: 100 Newly diagnosed patients of Depression as per ICD 10 (International classification of diseases) DCR (Diagnostic criteria for research) were selected for study after applying strict inclusion and exclusion criteria. Baseline Hamilton depression rating scale (HAMD) and baseline C reactive protein (CRP) was assessed and antidepressant treatment was started. After 8 weeks, again HAMD and CRP were assessed.Results: Mean of Baseline CRP was higher in patients in those who have no response after antidepressant treatment and it was significant. The relationship between baseline HAMD and baseline CRP was found to be significantly positively correlated. Mean HAMD was significantly reduced after 8 weeks of antidepressant treatment. Mean CRP was significantly reduced after 8 weeks of antidepressant treatment. The relationship between baseline CRP and reduction in HAM D (in baseline and after 8 weeks of treatment) found to be negatively correlated and it was significant.Conclusion: Escitalopram reduced C reactive protein in depressed patient and result was significant.